2017
DOI: 10.3390/ijerph14040418
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Biogenic Amines and Mycotoxins in Alfalfa and Red Clover Fodder Depending on Additives

Abstract: In the production of fermented feed, each crop can be contaminated with a variety of microorganisms that may produce natural pollutants. Biogenic amines, mycotoxins, and undesirable organic acids can decrease health feed safety. The aim of this study was to compare the counts of microorganisms, levels of biogenic amines, and the mycotoxins in forage legumes, and also to compare the occurrence of microorganisms and levels of mycotoxins in green fodder and subsequently produced silage and the influence of additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Then, the mini-silo was hermetically sealed and placed in the dark to prevent exposure to light, at a temperature of 28 • C ± 1 • C. Each container was equipped with a safety valve for the removal of excessive gaseous products [28,29]. After the lapse of the incubation time of 90 days [29], the micro-silages were opened and samples of them were homogenized. Subsequently, the samples were frozen and transported to the laboratory for chemical analyses and fermentation tests.…”
Section: Production Of Mixed Culture Silage-preparation Of Model Silagementioning
confidence: 99%
“…Then, the mini-silo was hermetically sealed and placed in the dark to prevent exposure to light, at a temperature of 28 • C ± 1 • C. Each container was equipped with a safety valve for the removal of excessive gaseous products [28,29]. After the lapse of the incubation time of 90 days [29], the micro-silages were opened and samples of them were homogenized. Subsequently, the samples were frozen and transported to the laboratory for chemical analyses and fermentation tests.…”
Section: Production Of Mixed Culture Silage-preparation Of Model Silagementioning
confidence: 99%
“…Zearalenone (ZEA) mainly comes from foods and feeds contaminated by several species of Gibberella and Fusarium [1]. These fungi contaminate cereal grains, including maize, wheat, sorghum, barley, and oats, and produce ZEA in the farm and field and, or during the period of harvesting and storage at a low temperature and high humidity [2,3,4]. In recent years, several studies have suggested that the structure of ZEA can be modified by microorganisms, plants, animals and humans via glycosylation, sulfation, and acetylation of trichothecenes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies suggest that the occurrence of NH 3 and BAEs also exists in substantially well‐preserved silages (Mlejnkova et al, 2016; Scherer et al, 2015; Skladanka et al, 2017), but available studies merely focused on the effect of different additives on the concentrations of NH 3 and BAEs, whilst information on functional micro‐organisms and active mechanisms remain mostly undescribed. Our previous findings showed that sucrose addition could effectively improve the fermentation quality of alfalfa silage (Li, et al, 2020; Zheng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%